NOTA SOBRE EL METABOLISMO DEL CITRATO EN CORAZON AISLADO DE TORTUGA - SODI PALLARES, ERNESTO; PISANTY, J; PERALTA, B (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1948)
Hearts of individuals who had died of heart failure, but who seemed to have healthy myocardia, were examined chemically A pentose, identified as L-lyxose, never found free in nature, was found It is postulated that L-lyxose is formed by the organism us
ASTRON J
Keywords: NOTA, METABOLISMO, CITRATO, CORAZON, TORTUGA; CIENCIAS DE LA VIDA; FISIOLOGIA HUMANA; FISIOLOGIA CARDIOVASCULAR